Enhancing the characteristics of hydrochar via hydrothermal carbonization of Korean native kenaf: The effect of ethanol solvent concentration as co-solvent and reaction temperature. (1st January 2023) - Youn, Hee Sun; Kim, Seong Ju; Kim, Ga Hee; Um, Byung Hwan
Graphical abstract: Highlights: HTC was carried out at various that ethanol concentration and reaction temperature for enhancing hydrochar properties. The water condition showed a higher carbon content and HHV than the ethanol solvent condition. The hydrochar of ethanol condition showed higher aromaticity than water condition in FT-IR. In SEM, it was confirmed that the ethanol solvent condition formed more particles than water. In hydrochar production, the ethanol condition was less efficient in enhancing properties than water due to leachinof phenolic component. Abstract: This study used hydrothermal carbonization to convert kenaf to produce hydrochar similar to coal and enhance fuel characteristics by reaction temperature (200–350 °C) and ethanol solvent concentration (0–100%). The chemical and fuel characteristics of the hydrochar were analyzed using scanning electron microscopy, fourier transform infrared spectroscopy, thermogravimetric analysis, calorimetry, and elemental analyzer. The carbon composition of hydrochar increased to 65.19%, while the ash composition decreased to nearly 0.05% at water100% compared with untreated kenaf. In addition, the higher heating value of hydrochar increased to 26.77 kJ g −1, resulting in an increase in energy densification to 1.61. Fuel properties such as carbon content and energy densification were further enhanced in hydrochar using only water solvent compared to ethanol. The hydrochar produced by water has a composition similar to that of lignite and bituminous coal. These results correlate with the severity of the process and the effect of kenaf decomposition by varying ethanol solvent concentration. The leaching of lignin by using ethanol as solvent; this with water promoted to decomposition of biomass through hydrolysis of cellulose and hemicellulose. Therefore, the combination of water and ethanol synergistically can help to reduce the condition of the kenaf decomposition process for enhancing hydrochar characteristics.